Geographical indication - Joshi, Bal Krishna; Gauchan, Devendra (NAGRC, 2020)
Agricultural products are generally associated with their place of production and are influenced by specific local, geographical factors such as climate and soil. A geographical indication (GI) is a sign (or name) used on products that have a specific geographical origin and possess unique qualities or a reputation associated with the product of the origin (WIPO 2004). The qualities, characteristics or reputation of the product should be essentially due to the place of origin. GI is an intellectual property that protects the product of the area and ultimately helps to promote conservation of agrobiodiversity on-farm and boost economy of local community. The well-known examples of GIs in South Asia include Darjeeling tea, Basmati rice, Himalayan water, Alphonso and Sindhri mangoes, Bhutanese red rice, Pakistani shu (wind proof woolen fabric) and Ajrak (designs from Sindh), jasmine (Hom Mali) rice. Until now, there is no any GI protected products in Nepal. Government of Nepal has approved the National Intellectual Property Right Policy (2017) which includes Copyrights, Patents, Industrial design, Trademarks, GI, Varietal protection, Trade secrets and Traditional knowledge policy (MoICS 2017). Among these policies, GI gives exclusive right to a region or a landscape (eg village, town, region or country) to use a name for a particular product with certain characteristics that corresponds to their specific location. There are more than 100 agricultural products (Joshi et al 2017) which have already established their reputation representing their GIs. Malla and Shakya (2004) have identified and listed 87 potential products for geographical indication (GI) protection in Nepal. Most of the products possess greater cultural and age-old traditional values. Important indigenous crop landraces and their products linked with particular geography, which should therefore, be protected with GI by developing suitable legislation for their market promotion, on-farm conservation and livelihood enhancement of local communities. For GI promotion, Geo-linked popular crop landraces and their traits need to be found out for their potential trade promotion and value addition.